O desenvolvimento econômico regional na região Sul do Brasil - Klein, Cristiane Fernanda (2017)
The objective of this research is to analyze the stage of economic development of the municipalities of the Southern Region of Brazil and its regional developments. The period of analysis is the years of 2005 and 2015, given the availability of data. The research problem was fostered in the intra-regional disparities that emerged during the development process of the Southern Region of Brazil. To obtain the results, data were collected that represented the social and economic development dimension, and from there, was used a methodology in which it builds an indicator of growth and regional development. This indicator provides a quantitative information system on the spatiality of underdevelopment and the dynamism of the municipalities of southern Brazil. The results pointed out that, despite the improvement in the Regional Economic Development Index (REDI) of most municipalities from 2005 to 2015, there are still striking inequalities in the development stage of the municipalities of the Southern Region of Brazil. The municipalities in the Developed stage presented good results in the partial indexes linked to the social dimension of development, including improvements and good results in the economic dimension, mainly linked to industry. On the other hand, the municipalities in Transition or considered of Low Dynamism, presented deficiency in some specific factors related to the particularity of each municipality. In addition, the Stagnant municipalities showed improvements in the partial indicators, but with significant deficiencies in the variables of the two dimensions of development, hindering the improvement of social and economic variables. It is observed that, in order to improve this situation, it is necessary to analyze the profile, potentialities and failures of each municipality, in order to obtain better development tools.